Weak Market Efficiency for Technology Stocks During The COVID-19 Pandemic - Ullanchiang Meillenia Tumbal; Robiyanto Robiyanto; Harijono Harijono (AJAR, 2023)
Many studies related to capital market efficiency have been carried out, but currently there is a lack of research on weak forms of market efficiency in other financial markets such as the technology market. The purpose of this study is to analyze the efficiency of the weak form of the market for technology stocks during the Covid-19Pandemic. The data used in this study is data on daily closing prices for technology stocks from 2020-2022 from the Indonesia Stock Exchange. This data is obtained from Yahoo Finance Technology. The analytical tool used is the Runs Test followed by the Augmented Dickey-Fuller and Correlogram for Robustness Checking. The results of this study state that there are several technology stocks that are included in the efficient form in a weak form, which means that the prices of these stocks during the Covid-19 Pandemic are random walk, so that technical analysis cannot be applied in analyzing several technology stocks, namely EMTK, MTDL and LUCK. The results of this study suggest that investors in trading EMTK, MTDL and LUCK shares do not use technical analysis.